Eksternalitas Keberadaan Trans Padang Koridor III sebagai Transportasi Publik - Al-Khairi, Muhammad Thariq; Yuliarti, Yuliarti (YASIN, 2025)
The increasing number of private vehicles and the limited availability of public transportation in Padang City have prompted the government to introduce a Bus Rapid Transit (BRT) system through the operation of Trans Padang, including Corridor III, which was officially launched in April 2024. This study aims to analyze the positive and negative externalities of Trans Padang Corridor III as a public transportation system. A descriptive qualitative approach was used, with data collected through field observations, semi-structured interviews with 17 informants, including representatives from the Department of Transportation, service users, angkot drivers, and the general public as well as document analysis. Data were analyzed through the stages of reduction, presentation, and conclusion drawing/verification, with data validity ensured through source triangulation. The findings indicate that negative externalities include traffic disruptions caused by bus operations on narrow roads such as Jalan Maransi, accident risks, and decreased income for city transport (angkot) drivers due to unequal competition. On the positive side, externalities include increased public access to essential facilities, reduced household transportation expenditures, and the stimulation of microeconomic activity around Trans Padang bus stops. The study concludes that participatory public transport policies based on actual infrastructure conditions are necessary to minimize negative impacts and optimize the socio-economic benefits of the BRT system. Recommendations include regular route evaluations, involving informal transport operators in planning, and improving road infrastructure to support a more inclusive and adaptive BRT operation.